Assessing network security - Lam, Kevin (Microsoft Press, 2004)
Help beat the hackers at their own game! Discover how to take charge of system assets through hands-on vulnerability scanning, penetration testing, and other advanced testing techniques--straight from members of the Microsoft Security Team.